PERSEPSI SANTRI PONDOK PESANTREN AL-JUNAIDIYAH BIRU TERHADAP PEMBELAJARAN PENANGGALAN MASEHI DAN HIJRIYAH - Nurul Wakia; Mustafa, Adriana; Uyuni, Hilyatul (UIN ALAUDDIN MAKASSAR, 2024)
Based on the information provided, the research examines the perception of students (santri) of Al-Junaidiyah Biru Islamic Boarding School towards the Gregorian and Hijri calendars. The research aims to address the following issues: Reality of Calendar Learning How is the learning of the Gregorian and Hijri calendars conducted in the formal Islamic education at Al-Junaidiyah Biru Islamic Boarding School, what is the perception and understanding of students at Al-Junaidiyah Biru Islamic Boarding School towards the Gregorian and Hijri calendars. The research methodology is field research (lapangan) utilizing a qualitative descriptive method. Data collection involves primary and secondary sources. Primary sources include literature such as books, journals, and dissertations that support the research. The findings suggest that students' perception of the Gregorian and Hijri calendars emphasizes their importance in relation to Islamic worship and daily life. The calendar curriculum is structured according to the Graduation Competence Standards (Standar Kompetensi Lulusan, SKL) established by the boarding school. The implications of the research propose that the curriculum on Islamic astronomy (ilmu falak) could be further developed based on the Ministry of Religious Affairs Regulation Number 13 of 2014 concerning Islamic Religious Education in Al-Junaidiyah Biru Islamic Boarding School. Additionally, it suggests the provision of instruments related to the calendar system within the boarding school. Overall, the study underscores the significance of calendar knowledge in Islamic education and highlights potential areas for curriculum enhancement and educational policy implementation within Al-Junaidiyah Biru Islamic Boarding School.